Long distance transport and welfare of farm animals [ - Appleby, Michael C. (CABI, 2008)
Brings together studies from several animal scientists and researchers to review the implications and necessity of long distance animal transport for slaughter. This title combines reports on regional practices with discussions of the science, economics legislation and procedures involved in this practice.